Economics of Wellbeing and Mental Health : A cost-of-illness analysis on Mental Health in Denmark - Becher, Hannah (2019)
The purpose of this thesis was to conduct a cross-sectional cost-of-suboptimal mental well-being analysis which estimates additional healthcare and non-healthcare costs of low and moderate compared to high mental well-being for the Danish society in 2017. Methods from conventional cost-of-illness studies were applied as well as an OLS regression. Necessary data came from a Danish survey on Mental Health and Well-being which was linked to Danish registries. Total healthcare and non-healthcare costs for low and moderate compared to high mental well-being were estimated to be € 1,552.6 million in 2017. Estimated additional costs suggest that it is not enough to merely measure the economic costs of classified mental disorders. Implications for the field of promotion in mental health and well-being were described. Another study has to be carried out to include more cost components.